On the power of words : (reflection on V. Havel's plays and essays on language and communication) - Roman Madecki (Opera slavica, 2024)
The paper deals with the phenomenon of the power of words, which is understood as the effect that a word used in a communicative act can produce. Considerable attention is already paid to it in biblical texts, in which the word is regarded as a manifestation of human power and a real act. The misuse of language leads to misunderstandings and conflicts with unfortunate consequences for individuals and society. Some theories from the philosophy of language also reflect this issue. K. Bühler speaks in this context about the conative function of language, J. L. Austin about the perlocutionary act. Václav Havel also noted this nature of words in his plays, essays and speeches. According to Havel, language has an ambivalent nature, because it can be used to create on the one hand, and to provoke conflict and destroy on the other. However, conflicts can also arise because of various communication barriers. These barriers can be the result of a deformation of the code, the impossibility of opening a communication channel, the absence of a relationship between the text and the extra-linguistic reality, or the loss of the speaker's identity. Conflict in this sense is understood very broadly, i.e. not only as a mismatch between people, but also as a conflict between the language code, its users and the world in which they move.